Studies on the Effect of Fruitlet Thinning on Crop Load and Biochemical Quality of Plum Cv. Kala Amritsari - Parveen; Dalal, R. P. S.; Kumari, Anita; Chetna (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was carried out during the year, 2022 and 2023 at experimental orchard, Department of Horticulture, Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana, India to improve the quality of plum fruit cv. Kala Amritsari through thinning of fruitlets under sub-tropical zone. The experiment was laid out in randomized block design with three replication consisting of ten thinning treatments viz. Ammonium thiosulphate (ATS) at 2.0%, and 4.0%; Benzyl Adenine (BA) at 150 and 300 ppm; Ethephon at 75 and 150 ppm; Hydrogen cyanamide at 0.4 and 0.8% and hand thinning. Chemical sprays were done just after fruit set (2 weeks after petal fall). The results of chemical and hand thinning were compared with unthinned trees (control). It might be concluded from the present study that among various fruit thinning chemicals and hand thinning treatments, Ethephon at 150 ppm applied 2 weeks after petal fall stage was found most effective in decreasing fruit load closely followed by ATS at 4.0% and Ethephon at 75 ppm. ATS at 4.0% applied 2 weeks after petal fall stage was found significantly most effective in thinning of fruitlets and enhancing the chemical fruit quality parameters such as total soluble solids (TSS), total sugars, reducing sugars, non-reducing sugars, pulp anthocyanin content and reducing acidity and pulp carotenoids content followed by treatment HCN at 0.8%.